13. GENOTYPE CHARACTERISTICS OF B. PSEUDOMALLEI STRAINS ISOLATED FROM CHILDREN DIAGNOSED WITH WHITMORE AT THE NATIONAL CHILDREN’S HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Background: Burkholderia pseudomallei is the main cause of Whitmore disease in humans and animals. It is mainly prevalent in tropical Southeast Asia and Northern Australia with a high mortality rate, the disease is likely to recur and cause persistent infection.Objective: To determine the genetic characteristics of B. pseudomallei strains isolated from pediatric patients with Whitmore disease treated at the National Children’s Hospital.Methods: The study was conducted at the National Children’s Hospital from 2017 to 2023. A total of 37 strains of B. pseudomallei were isolated and cultured from clinical samples of pediatric patients diagnosed with Whitmore disease. Illumina sequencing technology successfully sequenced the entire genome of 37 bacterial strains.Results: Among 37 B. pseudomallei strains, we detected 12 genotypes: ST67 was 10/37 strains (27%); ST221 and ST541 were 5/37 strains (13.5%); ST545 was 3/37 strains (8.1%); ST46, ST50, ST68, ST500, ST507, ST544 each had 1 strain. In addition, we also detected 1 strain with a new gene sequence belonging to the ST group with no information in the PubMLST database.Conclusions: Subgroup ST67 is the common genotype of B. pseudomallei isolated from children diagnosed with Whitmore in the Northern provinces of Vietnam. This is the first study in Vietnam to publish a large number of whole genome sequences of B. pseudomallei strains.
Keywords: Whitmore disease; B. pseudomallei strains; sequence type; children